REVITALISASI PASAR TRADISIONAL SEBAGAI UPAYA DALAM MENINGKATKAN PENERIMAAN RETRIBUSI PASAR DAN KESEJAHTERAAN PEDAGANG - Amalia, Dini Rizky; Asmini, A (Pusat Riset dan Publikasi, 2024)
This study aims to know the effect of market revitalization on traders’ welfare and market retribution at Seketeng traditional market, Sumbawa Besar. The type of this study was associative study. The type of data used was quantitative and qualitative data. The Sources of data in this study were primary and secondary data. The total of populations were 691 respondents. The technique of determining sample was Slovin formula. The numbers of samples were 87 samples. The method used to collect data were questionnaire and documentation. The data analysis tool used was simple linear regression. The results of study showed that partially market revitalization had significant effect on traders’ in traditional Seketeng Market Sumbawa Besar, it was based on the t-value was higher than t-table (5.024> 1.988) with significant value of was 0.000 was lower than 0.05, furthermore, market revitalization had significant effect on market retribution, it was based on the t-value was higher than the t-table (5.024>1.988) with significant value of 0.000 was lower than 0.05, then the value of the coefficient of determination or r square was 0.229 thus the percentage effect of revitalization market on the welfare of traders and market retribution in traditional Seketeng market was 22.9% while the remaining of 77.1% was affected by other variables outside of this study.